SURVEI BURNOUT PADA MAHASISWA KEPERAWATAN YANG MENJALANI SISTEM PEMBELAJARAN BLOK DI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Ida Ayu Mas Prabhasuari; Indah Mei Rahajeng; I G A Pramitaresthi (Coping: Community of Publishing in Nursing, 2021)
Burnout is a psychological condition caused by physical, emotional, mental exhaustion that causes prolonged stress. Burnout can be experienced by students who are struggling to catch up with their study activities and their academic demand. The aim of this study to examine burnout in nursing students undergoing a block learning system at Medical School Udayana University. This research is a descriptive quantitative study with cross sectional approach. This study used non-probability sampling technique using total sampling. Samples were 245 respondents. The conclusion appear that the most of students were female (89.4%), enrolled according to their interests (72.7%), class of 2019 with the highest number of respondents (70 people). The average value of burnout based on the dimensions of burnout are 1) emotional exhaustion (16.09), 2) Disbelief (7.30), 3) Professional effectiveness (19.12). The majority of students with a higher average burnout score were male students (44.2), in group of students who were not interests to the nursing subjects (47.3), class of 2017 (44.6). The majority students who have the highest average in burnout are male, in group of students who were not passionate in nursing major, and third year students.